1979
DOI: 10.1002/jcu.1870070410
|View full text |Cite
|
Sign up to set email alerts
|

Cancer therapy with ultrasound: A historical review

Abstract: The 45-year history of research in cancer therapy involving ultrasound may be divided into the four periods of initiation, enthusiasm, pessimism and revival. There have been three approaches to the subject: studies have sought to measure the effects on tumors of a) ultrasound alone; b) ultrasound in combination with radiotherapy, and c) ultrasound in combination with chemotherapy. With the first approach the results have varied. In some cases, decreased growth rates or regressions of tumors have been reported;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(60 citation statements)
references
References 48 publications
(2 reference statements)
0
60
0
Order By: Relevance
“…Thus, hyperthermia for anticancer treatment could inhibit tumor cell proliferation by destroying cancer cells or making them more sensitive to the effects of conventional antitumor therapies, such as radiation or chemotherapy. 3 Various heating sources ranging from radiofrequency to microwaves, 4,5 as well as ultrasound waves, 6 have been used to produce moderate heating in a specific target region. However, the use of heating sources conventionally employed for hyperthermia is limited because of the damage they cause to surrounding healthy tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, hyperthermia for anticancer treatment could inhibit tumor cell proliferation by destroying cancer cells or making them more sensitive to the effects of conventional antitumor therapies, such as radiation or chemotherapy. 3 Various heating sources ranging from radiofrequency to microwaves, 4,5 as well as ultrasound waves, 6 have been used to produce moderate heating in a specific target region. However, the use of heating sources conventionally employed for hyperthermia is limited because of the damage they cause to surrounding healthy tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound has been used clinically for many years (Kremkau, 1979). Several publications have described the use of ultrasound for enhancing transdermal permeation of drugs applied topically (Levy et al, 1989;Bommannan et al, 1992a,b).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, methods to increase the penetration of ALA are needed. Ultrasound has been used in the treatment of cancer (Kremkau, 1979). It has been reported that ultrasound irradiation increased the transdermal permeation of drugs such as inulin and mannitol in rats by 5-to 20-fold within 1 to 2 hr following ultrasound application (Levy et al, 1989;Bommannan et al, 1992a).…”
mentioning
confidence: 96%
“…The in vivo data for neurogenic tumours are also sparse (SUTTON 1971, KREMKAU 1979, MAGIN & JOHNSON 1979, T H U N I N G et coll. 1980, WALLEN et coll.…”
Section: From T H E Departmentsmentioning
confidence: 99%